Trends in Diagnosis of Alpha-1 Antitrypsin Deficiency Between 2015 and 2019 in a Reference Laboratory - Belmonte, Irene (Int J Chron Obstruct Pulmon Dis, 2020)
BACKGROUND: Alpha-1 antitrypsin deficiency (AATD) remains largely underdiagnosed despite recommendations of healthcare institutions and programmes designed to increase awareness. The objective was to analyse the trends in AATD diagnosis during the last 5 years in a Spanish AATD reference laboratory. METHODS: This was a retrospective revision of all alpha-1 antitrypsin (AAT) determinations undertaken in our laboratory from 2015 to 2019. We analysed the number of AAT determinations performed and described the characteristics of the individuals tested, as well as the medical specialties and the reasons for requesting AAT determination. RESULTS: A total of 3507 determinations were performed, of which 5.5% corresponded to children. A significant increase in the number of AAT determinations was observed from 349 in 2015 to 872 in 2019. Among the samples, 57.6% carried an intermediate AATD (50–119 mg/dL) and 2.4% severe deficiency (<50 mg/dL). The most frequent phenotype in severe AATD individuals was PI*ZZ (78.5%), and aminotransferase levels were above normal in around 43% of children and 30% of adults. Respiratory specialists requested the highest number of AAT determinations (31.5%) followed by digestive diseases and internal medicine (27.5%) and primary care physicians (19.7%). The main reason for AAT determination in severe AATD adults was chronic obstructive pulmonary disease (41.7%), but reasons for requesting AAT determination were not reported in up to 41.7% of adults and 58.3% of children. CONCLUSION: There is an increase in the frequency of AATD testing despite the rate of AAT determination remaining low. Awareness about AAT is probably increasing, but the reason for testing is not always clear.